PTU-125 Factors influencing increased ERCP brushing sensitiviy in pancreaticobiliary malignancy: a single centre experience. (June 2019) - Varmpompitis, Ioannis; Griffiths, Cameron; McEvoy, Sinead; Booth, Jonathan; Chandra, Nishchay
Abstract : Introduction: Biliary brushings are often the only way to confirm a diagnosis of malignancy in patients presenting with biliary strictures. There is a paucity of data regarding the parameters that may affect the diagnostic yield of this technique. The aim of this study was to identify key factors that may improve diagnostic sensitivity in hepatobiliary malignancies. Methods: Brushing outcomes were identified over a 2-year period and analysed by demographic factors (age, sex), indication of the procedure, site and length of stenosis on ERCP, CBD dilatation on CT/MRCP/ERCP, site and size of mass, laboratory values (ALP, ALT, bilirubin) prior to the procedure, and final outcome (histologically or radiologically confirmed). We calculated the ratio of at least suspicious for malignancy results out of the total cases of malignancies. Final outcome was defined by histology or radiological evidence of cancer in the follow-up period. Data was retrospectively retrieved and processed using the EPR (electronic patient record) hospital database and the radiology InSight PACS system. Data was analysed using the statistical package SPSS v.25. Results: A total of 59 brushing results were identified over the period 01/2017–01/2019. 52 (88.1%) were malignant and 7 (11.9%) were benign. The mean age was 71.4 yrs and the majority of malignancies were pancreatic cancer (33/52; 63.5%), with the remainder including cholangiocarcinoma (7), ampullary cancer (6) and other malignancies. Forty of 52 cases were true positives, indicating a sensitivity of 76.9%, while the specificity was 100% (no false negative and 7/7 true negative). Among the factors examined, sensitivity was significantly associated with the site of stenosis (89.2% for distal vs. 50% for mid and mid-distal stenoses, p=0.023), and with the mass being in the pancreatic head versus in the uncinate process (84.6 vs 40%, p=0.029). Sensitivity was higher for longer strictures (63.6% vs 46% for strictures >1.9 cm (i.e. the median value), and for larger masses (mean size of mass 4 cm in true positive vs 2.6 cm in false negatives) but these results did not reach statistical significance. The age, CBD dilatation on imaging, type of cancer and the laboratory markers before the procedure were not associated with differences in the diagnostic yield. Conclusions: Distal CBD stenoses and pancreatic head lesions are associated with statistically significant increase in brushing sensitivity for malignancy. This study suggests that in the absence of a distal CBD stricture or a pancreatic head lesion, further investigation modalities (additional brushings, EUS, percutaneous biopsy, cholangioscopy) will be more likely required to achieve diagnostic certainty.